Analisis Kost Makan Santri Dalam Manajemen Proses Bisnis Untuk Mengoptimalkan Produktivitas, Efesiensi Dalam Menunjang efektifitas Kegiatan Santri - Ahmad Zainullah; Jeni Susyanti (Publikasi Inspirasi Indonesia, 2024)
Kos makan santri play an important role in supporting the welfare, productivity, and efficiency of santri learning time in pesantren. Programs such as kos mara at Nurul Jadid Islamic Boarding School are examples of successful initiatives in regulating santri consumption patterns and increasing the economic stability of the pesantren. The relationship between efficiency, effectiveness and productivity is an important focus in achieving the objectives of santri activities in pesantren. This research uses a qualitative descriptive approach to explain or analyze the boarding school meal cost in business process management to optimize productivity, efficiency in supporting the effectiveness of student activities at Nurul Jadid Islamic Boarding School.